A critique of Humean and anti-Humean metaphysics of cause and law - Smart, Benjamin T. H. (2012)
It is my contention that physics and metaphysics (or at least the aspects of metaphysics to be considered in this thesis) broadly strive to achieve common goals: to understand what our physical system is constituted by, and both how, and why it evolves in the way that it does. Metaphysicians, as well as the scientific disciplines, play an important role in our understanding of the universe. In recent years, physicists have focussed on finding accurate mathematical formalisms of the evolution of our physical system - if a metaphysician can uncover the metaphysical underpinnings of these formalisms; that is, why these formalisms seem to consistently map the universe, then our understanding of the world and the things in it is greatly enhanced. Science, then, plays a very important role in our project, as the best scientific formalisms provide us with what we, as metaphysicians, should be trying to interpret – but these interpretations are integral to understanding the nature of natural laws and causation.